Green Synthesis Of AgNPs Dispersed 3-Armed Gly Lac Macromolecule Matrix And Pla Film For Its Antimicrobial Activities - Yodahe, Gonfa (ASTU, 2021)
Green nanoparticles synthesis method from leaves extract revealed full an economical, sustainable and eco-friendly method. Here we used leaf extract of Vernonia amygdalina for the synthesis of silver nanoparticles (AgNPs) as reducing and capping agents. Mixed Methanol with Distilled Water (M/DW) was selected from different solvents used for the effective extraction process. The effect of different operational parameters (Solvent ratio of M/DW, Precursor concentration, ratio of AgNO3/plant extract, Temperature, Time and pH) on the synthesis of AgNPs was carried out. Among them, the effect of pH was confirmed as the dominant one that affects the chemistry of the solution. The synthesized AgNPs were homogeneously dispersed in GLY-LAC macromolecule and used as filler to prepare PLA based biofilms. Greenly synthesized AgNPs were confirmed using UV-Vis spectroscopy and characterized by XRD and FT-IR. Besides, its antimicrobial activities were also evaluated. The UV-Vis spectra showed specific Surface Plasmon Resonance (SPR) absorption peaks between 411 nm- 430 nm for synthesized AgNPs at optimum conditions. It revealed that the presence of AgNPs in the reaction solution. XRD peaks observed at 2θ are in the range of (30°-80°), which corresponds to the reflection of the plane of crystallinity of AgNPs. Phytochemical screening test and FT-IR analysis of V. amygdalina leaves extract revealed the existence of phenolic, Tannin, saponins and flavonoid groups, which capped the nanoparticles during the synthesis. The antibacterial activities of synthesized AgNPs were evaluated against Gram-positive bacteria (S. pyogenes and S. aureus) and Gram-negative bacteria (E. coli and P. aeruginosa) and observed that a higher zone of inhibition. This study results finally revealed that the antimicrobial activity of GLY-LAC/ PLA biofilms enhanced with the dispersion of green synthesized AgNPs. Hence, it suggests that AgNPs dispersed GLY-LAC/PLA could be used to prepare different materials for packaging wound dressing, textile industries, etc.
Keywords: Vernonia amygdalina, Phytochemical analysis, Silver nanoparticles, AgNPs/GLY-LAC bioconjugate, AgNPs/GLY-LAC/PLA biofilm.